Sabkha ecosystems Volume III : Africa and Southern Europe - Ozturk, Munir A. (Munir Ahmet) (Tasks for vegetation science, 2011)
This book is part of "Sabkha Ecosystems series". The series is designed to provide information on sabkha ecosystems of different regions. It will add to the collective knowledge available about saline ecosystems and also focuses on the African region where only limited information is currently available on.